Audit of triage tools to recognise seriously ill children with fever: should we change?. (4th April 2011) - Balogun, S; Boyd, C; Miller, C; Bowron, R; Mellon, A F
Abstract : Aims: Evaluation of 'NICE' Traffic Light (NTL) assessment of febrile children and a tool1 based on abnormalities of one or more key vital signs (VS+). To aid to our department in identifying seriously ill children, including validation on a group of patients with meningococcal disease. Design: Group (1) Children with fever >38°C in (a) Paediatric Emergency Department (PED) or (b) Walk-In-Centre (WIC) January 2010, Group (2) Children with meningococcal disease (2006–2009). Data was collected at time of presentation to categorise into red, amber or green (NTL), and to establish as VS+ or VS-. Outcome measures: (1) Referral from WIC (including self referral) or PED for further care. (2) Sensitivity and specificity of NTL and VS for serious/intermediate infection. Results: Data was analysed from 133 children (30 WIC, 31 PED, 36 meningococcal); 38.8% under 1 year old, 7.4% over 11 years. WIC: 63.5% were categorised green using NTL. 23.4% of these patients were either referred or later presented to PED/GP, whereas 6.7% were categorised red, none of whom were referred. 47% VS+ were referred compared to 16.7% VS-. PED: 50% were NTL green, 11.1% admitted to the ward for treatment. 13.4% were red, 50% admitted. 28% VS+ and 7.1% VS- were admitted. Meningococcal: 91.7% were categorised as red/amber, 8% as green but with three abnormal VS out of four. Four patients who were VS- were 'red' using NTL. Conclusion: NTL and VS have similar sensitivity and specificity for serious illness and may have a valid role in some primary and secondary care settings. Three versus four (8% vs 11%) with meningococcal disease would have been under-triaged based on NTL/VS alone. VS may be more useful in primary care than NTL and add value to NTL in assessing febrile children with higher prevalence of serious illness presenting in secondary care.